Design and Performance Analysis of Perovskite Solar Cell - Kumar, Ayush; Pandey, Saurabh kumar (2018 International Conference on Numerical Simulation of Optoelectronic Devices (NUSOD), 2018)
Searching for solar-absorbing materials comprising earth-abundant materials with chemical stability is of the critical importance of evolving photovoltaic technologies. The Mott-Hubbard type transition-metal oxides (TMOs) generally contain only earth-abundant elements and intrinsically have long-term chemical stability, which is ideal for constructing low-cost and resilient photovoltaic devices. In this study, different aspects of constituent layer parameters thickness, defect density buffer layers has been considered to identify the device performance of perovskite solar cell. An efficiency of 21.67% (with Voc of 0.93 V, Jsc of 26.65 mA/cm2 and fill factor of 0.87) has been achieved with TiO 2 based buffer layer.